2020
DOI: 10.1212/wnl.0000000000009977
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of EEG in prodromal dementia with Lewy bodies

Abstract: Objective:Early biomarkers for dementia with Lewy bodies (DLB) are still lacking. To determine whether electroencephalography (EEG) differentiates the prodromal phase of DLB from other causes of mild cognitive impairment (MCI) and whether EEG is predictive for time to conversion from MCI to DLB, we compared EEGs and clinical follow-up of patients with MCI due to DLB with MCI due to Alzheimer’s disease (MCI-AD).Methods: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 37 publications
5
39
1
Order By: Relevance
“…Quantitative EEG findings of MCI-LB have been reported to be similar to those reported in DLB vs. AD, where MCI-LB have lower dominant frequency compared to MCI-AD [65][66][67]. This also translates into higher pre-alpha power and lower alpha and beta power and a higher theta/alpha ratio [65][66][67].…”
Section: Prodromal Dlb and Progression To Dementiasupporting
confidence: 59%
See 3 more Smart Citations
“…Quantitative EEG findings of MCI-LB have been reported to be similar to those reported in DLB vs. AD, where MCI-LB have lower dominant frequency compared to MCI-AD [65][66][67]. This also translates into higher pre-alpha power and lower alpha and beta power and a higher theta/alpha ratio [65][66][67].…”
Section: Prodromal Dlb and Progression To Dementiasupporting
confidence: 59%
“…AD, where MCI-LB have lower dominant frequency compared to MCI-AD [ 65 , 66 , 67 ]. This also translates into higher pre-alpha power and lower alpha and beta power and a higher theta/alpha ratio [ 65 , 66 , 67 ]. Schumacher 2020b reported that spectral power analyses had sensitivities of 23–51%, specificity of 81–97% and area under receiver operating characteristics curve (AUROC) of 0.54–0.71 in diagnosing MCI-LB ( Table 4 ) [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative or visually assessed EEG differentiates DLB from AD with high sensitivity and specificity and may correlate with cognitive changes, fluctuations, and hallucinations in DLB [ 62 , 63 ]. EEG also may have a role not only in diagnosing MCI-LB, with slower frequencies in pre-alpha and theta ranges compared to healthy controls and intermittent delta activity patterns differentiating MCI-LB from MCI-AD, but also in predicting conversion from MCI-LB to DLB [ 64 , 65 ]. While potentially less costly and less invasive than some biomarker studies, use of EEG as a diagnostic or prognostic biomarker for LBD will require increased standardization, understanding of inter-individual variability, integration with imaging and biofluid markers, and larger-scale prospective studies.…”
Section: Optimizing Clinical Trial Design In Lbd (Table 2 mentioning
confidence: 99%